New Coordinates of Accounting Academic Education. A Romanian Insight - Victoria Stanciu; Irina Bogdana Pugna; Mirela Gheorghe (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research question: Are accounting graduates prepared to face IT developments in their profession? Motivation: The accounting profession is facing a rapid transformation involving digital technology that implies significant changes. "Modern accountants are expected to have a high level of IT knowledge and skills and towards that direction the curriculum in accounting education have to adopt a wide range of modules in order to provide accounting students with the required competencies" (El-Damarleh, 2017: 202). Today's students are digital natives and they "think and process information fundamentally differently from their predecessors" (Prensky, 2001: 1). Academic education needs to adapt to the language of digital natives and provide them with new skills and the knowledge required by the profession. Idea: We aim to investigate the awareness of bachelor students in accounting regarding the impact of IT on accounting processes and their preparedness in this regard. Tools: Data was collected using a multiple-choice questionnaire distributed to third-year and master's accounting students at the Bucharest University of Economic Studies. Data was analyzed using Excel. Findings: The students are aware of the importance of the new technologies and applications relevant to the profession, but their knowledge needs to be improved. The current curriculum does not include important aspects of the new digital technology that are already embedded or being assimilated within the accounting profession. Contribution: The paper provides recommendations regarding accounting academic education, providing arguments for developing IT-related competencies for accounting students aiming to align their knowledge and skills to current and future professional requirements. The conclusions emphasize the need of a new approach in the accounting teaching and understanding of the accounting flows and processes in a high IT environment.
Keywords: A2; I25; M41; 650; accounting graduates; future of accounting profession; digital accounting; IT knowledge and skills